Inhibition of hypoxia-inducible factor activity with Carica papaya extracts - Shafee, Norazizah (2013)
An extract of Carica papaya leaves is used as an inhibitor of HIF to effectively block hypoxia-inducible factor (HIF) function and methods of use thereof. More specifically it relates to the use of Carica papaya plant extract to eliminate unwanted cells by inhibiting HIF in the prevention and treatment of hypoxia-related conditions and diseases such as inflammatory diseases, vascular diseases, cancer and infectious diseases. In a particular embodiment, a solid hypoxic tumor in a patient is treated by administering to the patient a therapeutically acceptable amount of an extract of Carica papaya leaves, preferably an alcohol extract such as a methanol extract, whereby to inhibit hypoxia-inducible factors in the tumor.